INFORMAL WAR-TIME INSTITUTIONS IN SCOPE OF KHARKIV REGION - Rabotyagova, Iryna (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The paper is devoted to the consideration of informal institutions in the Kharkiv region during a full-scale invasion, which are capable of determining not only the local political process and the characteristics of civil society, but also the course of military operations in the frontline region, as well as the trajectory of the longer process of democratization of Ukraine. In the study, institutions will be defined not so much as organizations, but as practices established in time and space that are decisive within the selected territory and society, whether or not organizationally fixed. In particular, both corruption and local public leadership traditional for pre-war Ukraine are considered, as well as informal institutions of martial law, such as local military leadership, informal practices of the mobilization process, the formation of the volunteer movement, including its military cluster. Informal institutions are studied as social practices stable in time and space, which have both a negative and a positive impact on the course of military operations in the Kharkiv region. Corruption is viewed in a broad sense not only as the appropriation of financial resources, but also as an informal, non-legal method of distributing and redistributing various goods and resources. The mobilization process is examined through the prism of social behavior, which includes human rights violations and backlash in the form of attacks or evadorship. An important obstacle to confronting the northern aggressor neighbor is the informal lines of division between the military and civilian sectors. The article also examines the phenomenon and organized forms of volunteering, both civilian and military, which is an important link in uniting the civilian and military population in the Kharkiv region, maintaining the front line in the region and providing primary assistance to temporarily displaced persons from the combat zone. Of particular importance in the context of the chosen topic is the aspect of borderline identity, which is both heterogeneous and changeable, contains elements of the local and European, the past and the present.